Method and device for manufacturing composite microporous copper-aluminum current collector

By forming copper and aluminum layers on both sides of the polymer film, the electrochemical instability and safety hazards caused by copper-aluminum current collector in lithium-ion batteries are solved, and more stable battery performance is achieved.

CN119208616APending Publication Date: 2024-12-27RONGENE NEW MATERIALS (BEIJING) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411292774.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing composite microporous copper-aluminum current collectors are used as the positive and negative current collectors in lithium-ion batteries, resulting in electrochemical instability and safety hazards. Aluminum is dissolved in the electrolyte, and copper is also dissolved, causing the battery to be unable to do so. Works normally.

Method used

Using polymer polymer film as the substrate, copper and aluminum layers are formed on both sides of the film through corona, inkjet printing, magnetron sputtering and vacuum evaporation, and copper is plating through ultrasonic cleaning and electrodeposition. , ensure that the copper layer serves as the negative electrode and the aluminum layer serves as the positive electrode to avoid electrochemical corrosion.

Benefits of technology

By optimizing the position and structure of the copper and aluminum layers, electrochemical corrosion is avoided, electrochemical stability is improved, safety hazards are eliminated, and the battery is operated normally.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208616A_ABST
    Figure CN119208616A_ABST
Patent Text Reader

Abstract

The invention discloses a manufacturing method and device of a composite microporous copper-aluminum current collector, and particularly relates to the field of current collectors for secondary ion batteries, the manufacturing method of the composite microporous copper-aluminum current collector comprises the following steps: step 1, a high-molecular polymer film is used as a base material, micropores are formed in the high-molecular polymer film, and the composite microporous copper-aluminum current collector is obtained; the dyne value of the surface of the high-molecular polymer film is set to be 32 mN / m, and the A face of the high-molecular polymer film is processed through a corona machine; and 2, printing an alcohol-soluble ink layer on the A surface of the high-molecular polymer film by using an ink-jet printer. The copper layer and the aluminum layer are optimized to be located on the two side faces of the high-molecular polymer film, the copper layer serves as a negative electrode current collector, the aluminum layer serves as a positive electrode current collector, after the battery is assembled through electron insulation of the film, the copper layer and the aluminum layer cannot be subjected to electrochemical corrosion, the electrochemical stability is improved, and potential safety hazards are eliminated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of current collectors for secondary ion batteries, and more specifically, to a method and device for manufacturing a composite microporous copper-aluminum current collector. Background Art

[0002] Lithium-ion batteries are widely used in new energy vehicles due to their high energy density and good cycle stability. The current collector plays multiple roles in lithium-ion batteries, including conducting electrons, supporting active materials, helping to dissipate heat, reducing internal resistance, and improving safety and economy. At present, new energy vehicles are still facing problems such as the need to improve weight energy density and reduce costs. As an inactive material, the current collector accounts for about 15% of the battery weight and about 10% of the battery cost. There is great potential to improve battery performance by optimizing the current collector.

[0003] In the prior art, copper-aluminum current collectors are prepared by coating an adhesive on the surface of copper foil and aluminum foil, and rolling to form a copper-aluminum current collector, or directly hot-pressing the copper foil and aluminum foil to form a copper-aluminum current collector, or using an electroplating method to plate copper on the surface of the aluminum foil or aluminum on the surface of the copper foil.

[0004] However, copper-aluminum composite current collectors, copper and aluminum serve as both positive and negative current collectors. When the battery is charging, aluminum will dissolve in the electrolyte, and when the battery is discharging, copper will dissolve in the electrolyte, which will lead to serious electrochemical instability and safety hazards, making the battery unable to work normally, posing a huge risk. Summary of the invention

[0005] The present invention provides a method and device for making a composite microporous copper-aluminum current collector, and aims to solve the following problem: in the existing method for making a composite microporous copper-aluminum current collector, copper and aluminum are used as positive electrode current collectors and negative electrode current collectors at the same time. When the battery is charged, aluminum will dissolve in the electrolyte, and when the battery is discharged, copper will dissolve in the electrolyte, which will lead to serious electrochemical instability and safety hazards, making the battery unable to work normally, posing a great risk.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a composite microporous copper-aluminum current collector, comprising the following steps:

[0007] Step 1: using a polymer film as a substrate, the polymer film is provided with micropores, setting the dyne value of the surface of the polymer film to 32 mN / m, and using a corona machine to process the A surface of the polymer film;

[0008] Step 2: Printing a layer of alcohol-soluble ink on the A side of the polymer film using an inkjet printer;

[0009] Step 3: Plating a copper layer on the A side of the polymer film by magnetron sputtering, the target material is pure copper with a purity of 99.99%;

[0010] Step 4: Put the polymer film into an ultrasonic cleaning machine for the first cleaning, and set the cleaning solvent to ethanol. The alcohol-soluble ink layer on the A side of the polymer film and the copper layer on the surface of the alcohol-soluble ink layer are cleaned to expose the polymer film;

[0011] Step 5: placing the polymer film in an electroplating solution for copper electroplating, wherein the apparent current density in the electroplating solution is 2A / cm2, and the electroplating time is 27 to 45 minutes;

[0012] Step 6: Place the polymer film in an ultrasonic cleaning machine for a second cleaning, and set the cleaning solvent to ethanol;

[0013] Step 7: Turn over the polymer film, and repeat steps 1 and 2 to process the B side of the polymer film;

[0014] Step 8: Plating an aluminum layer on the B side of the polymer film by vacuum evaporation;

[0015] Step 9: Repeat step 4 to perform ultrasonic cleaning on the B side of the polymer film, and the alcohol-soluble ink layer on the B side of the polymer film and the aluminum layer on the surface of the alcohol-soluble ink layer are cleaned to expose the polymer film;

[0016] Step 10: Drop the reagent on the upper surface of the composite microporous copper-aluminum foil, stick a piece of PH test paper on the lower surface of the composite microporous copper-aluminum foil, observe the color change time of the PH test paper, and cut the composite microporous copper-aluminum foil for tensile strength test.

[0017] In a preferred embodiment, the dyne value of the alcohol-soluble ink layer on the surface of the polymer film in step 2 is 36mN / m±1mN / m; the diameter of the circular spot of the alcohol-soluble ink layer is 0.1 to 10um, and the horizontal or vertical distance of the circular spot of the alcohol-soluble ink layer is 0.4 to 40um.

[0018] In a preferred embodiment, in step three, the distance between the target and the substrate is 40 mm to 60 mm, the sputtering power is 4.5 kW to 6.5 kW; and the thickness of the copper layer is 50 to 60 nm.

[0019] In a preferred embodiment, the ultrasonic power of the ultrasonic cleaning machine in step 4 is 0.5 to 1.5 KW, and the ultrasonic time is 1 to 3 min.

[0020] In a preferred embodiment, the electroplating solution in step five uses deionized water as solvent, and is stirred and prepared according to the concentration of CuSO4 of 200g / L and the concentration of concentrated H2SO4 of 60g / L; the electroplating copper uses 99.99% pure copper as the anode target, and the copper-plated film after S4 treatment is placed in the electroplating solution for electroplating copper, the apparent current density is 2A / cm2, and the electroplating time is 27 to 45min; the thickness of the copper layer is 1.5 to 2.5um.

[0021] In a preferred embodiment, the reagent in step ten is a lithium ion electrolyte. The electrolyte is dripped on the upper surface of the composite microporous copper-aluminum foil with a pipette, and a piece of PH test paper is attached to the lower surface of the composite microporous copper-aluminum foil. The color change time of the PH test paper is observed to perform lithium ion electrolyte permeability detection.

[0022] A device used in a method for making a composite microporous copper-aluminum current collector comprises a support table, on which a processing station and a driving mechanism are arranged, the processing station is used to place an object to be tested, the driving mechanism comprises a moving seat, on which a regulating mechanism is arranged, the regulating mechanism comprises a sleeve, and the sleeve makes the object to be tested fit tightly with the bottom of the sleeve by applying downward pressure, a visual recognition instrument is arranged in the support table, and a collection end of the visual recognition instrument is arranged toward the sleeve.

[0023] In a preferred embodiment, the processing station includes a support seat, a through hole 1 is formed on the support seat, a hole 2 is formed on the support platform, through hole 1 is connected to through hole 2, and transparent glass is slidably arranged in the support seat.

[0024] In a preferred embodiment, the driving mechanism includes a linear drive 1, which is fixedly arranged on the support table, a linear drive 2 is slidably arranged on the output shaft of the linear drive 1, and a movable seat is fixedly arranged on the output shaft of the linear drive 2.

[0025] In a preferred embodiment, the regulating mechanism includes a connecting pipe, the connecting pipe is fixedly arranged on the movable seat, the sleeve is fixedly connected to the connecting pipe, and a flexible gasket is fixedly arranged at the bottom end of the sleeve.

[0026] The beneficial effects of the present invention are:

[0027] The present invention optimizes the copper layer and the aluminum layer so that they are located on two sides of a high molecular polymer film, with the copper layer serving as a negative electrode current collector and the aluminum layer serving as a positive electrode current collector. The film insulates electrons, and after being assembled into a battery, electrochemical corrosion will not occur to the copper layer and the aluminum layer, thereby improving electrochemical stability and eliminating potential safety hazards. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the microstructure of the high molecular polymer film of the present invention.

[0029] Figure 2 This is a schematic diagram of the structure of the alcohol-soluble ink layer printed on the A side of the high molecular polymer film in step 2 of the present invention.

[0030] Figure 3 This is a schematic diagram of the structure of the copper-plated layer on the A side of the polymer film after magnetron sputtering in step three of the present invention.

[0031] Figure 4 This is a schematic diagram of the structure after cleaning the A side of the polymer film in step 4 of the present invention.

[0032] Figure 5 Schematic diagram of the structure of the aluminum layer on the B side of the polymer film after vacuum evaporation in step eight of the present invention.

[0033] Figure 6 It is a schematic structural diagram of the cross section of the composite microporous copper-aluminum foil of the present invention.

[0034] Figure 7 It is a schematic diagram of the process of the production method of the present invention.

[0035] Figure 8 It is a schematic diagram of the three-dimensional structure of the support platform of the present invention.

[0036] Fig. 9 It is a schematic diagram of the cross-sectional structure of the sleeve of the present invention from the front view.

[0037] The accompanying drawings are marked as follows: 1. polymer film; 11. micropores; 12. alcohol-soluble ink layer; 2. copper layer; 3. aluminum layer; 4. support platform; 5. processing station; 51. support seat; 52. transparent glass; 6. driving mechanism; 61. linear drive one; 62. linear drive two; 63. moving seat; 7. regulating mechanism; 71. connecting pipe; 72. sleeve; 8. visual recognition instrument. DETAILED DESCRIPTION

[0038] The present application is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0039] Refer to the instruction manual Figures 1 to 7 A method for preparing a composite microporous copper-aluminum current collector comprises the following steps:

[0040] Step 1: using a polymer film 1 as a substrate, the polymer film 1 is provided with micropores 11, setting the dyne value of the surface of the polymer film 1 to 32mN / m±1mN / m, and using a corona machine to process the A surface of the polymer film 1; the model of the corona machine is HSDY1000, and the corona parameters of the corona machine are: electrode gap: 1 to 2mm; corona voltage: 5000 to 15000V; corona power: 2 to 4kw; corona speed 5 to 15m / min. After the corona treatment, the dyne value of the surface of the polymer film 1 is 38 to 44mN / m;

[0041] Step 2: using an inkjet printer to print a layer of alcohol-soluble ink layer 12 on the A surface of the polymer film 1; the dyne value of the alcohol-soluble ink layer 12 on the surface of the polymer film 1 is 36 mN / m±1 mN / m; the diameter of the circular spot of the alcohol-soluble ink layer 12 is 0.1 to 10 um, and the horizontal or vertical distance of the circular spot of the alcohol-soluble ink layer 12 is 0.4 to 40 um;

[0042] Step 3: A copper layer 2 is plated on the A surface of the polymer film 1 by magnetron sputtering, and the target material is pure copper with a purity of 99.99%; the process conditions of the magnetron sputtering method are: background vacuum 4×10-4Pa~6×10-4Pa, sputtering gas pressure 0.2Pa~0.4Pa, the distance between the target material and the substrate is 40mm~60mm, and the sputtering power is 4.5kW~6.5kW; the thickness of the copper layer 2 is 50 to 60nm.

[0043] Step 4: Put the polymer film 1 into an ultrasonic cleaning machine for the first cleaning, and set the cleaning solvent to ethanol. The alcohol-soluble ink layer 12 on the A side of the polymer film 1 and the copper layer 2 on the surface of the alcohol-soluble ink layer 12 are cleaned to expose the polymer film 1; the ultrasonic power of the ultrasonic cleaning machine is 0.5 to 1.5 KW, and the ultrasonic time is 1 to 3 minutes. After cleaning, the A side of the polymer film 1 is as follows: Figure 3 As shown;

[0044] Step 5: Place the polymer film 1 in the electroplating solution for electroplating copper, the apparent current density in the electroplating solution is 2A / cm2, and the electroplating time is 27 to 45min; the electroplating solution uses deionized water as a solvent, and is stirred and prepared according to the concentration of CuSO4 of 200g / L and the concentration of concentrated H2SO4 of 60g / L; the electroplating copper uses 99.99% pure copper as the anode target, and the copper-plated film treated with S4 is placed in the electroplating solution for electroplating copper, and the apparent current density is 2A / cm 2 The electrodeposition time is 27 to 45 minutes; the thickness of the copper layer 2 is 1.5 to 2.5 um.

[0045] Step 6: Place the polymer film 1 in an ultrasonic cleaning machine for a second cleaning, wherein the cleaning solvent is set to ethanol; the ultrasonic power of the ultrasonic cleaning machine is 0.5 to 1.5 KW, and the ultrasonic time is 1 to 3 minutes, to produce an A-side composite microporous copper foil.

[0046] Step 7: Turn over the polymer film 1, repeat steps 1 and 2 to process the B side of the polymer film 1; set the dyne value of the surface of the polymer film 1 to 32mN / m±1mN / m, and use a corona machine to process the B side of the polymer film 1; the model of the corona machine is HSDY1000, and the corona parameters of the corona machine are: electrode gap: 1 to 2mm; corona voltage: 5000 to 15000V; corona power: 2 to 4kw; corona After corona treatment at a corona speed of 5 to 15 m / min, the dyne value of the surface of the polymer film 1 is 38 to 44 mN / m; a layer of alcohol-soluble ink layer 12 is printed on the B surface of the polymer film 1 using an inkjet printer; the dyne value of the alcohol-soluble ink layer 12 on the surface of the polymer film 1 is 36 mN / m±1 mN / m; the diameter of the circular spot of the alcohol-soluble ink layer 12 is 0.1 to 10 um, and the horizontal or vertical distance of the circular spot of the alcohol-soluble ink layer 12 is 0.4 to 40 um.

[0047] Step 8: Aluminum layer 3 is plated on the B surface of the polymer film 1 by vacuum evaporation; the model of the vacuum evaporation equipment is 2H1800, and the evaporation process conditions are: number of crucibles 6; evaporation rate 8g / min; winding speed: 2.5 to 7.5m / min; aluminum layer thickness: 0.97 to 2.90um; a schematic diagram of the aluminum layer 3 on the surface of the polymer film 1 after aluminum layer 3 is shown in Figure 5 The entire surface of the high molecular polymer film 1B, including the surface of the alcohol-soluble ink layer 12 and the ink spots, is coated with an aluminum layer 3.

[0048] Step 9: Repeat step 4 to perform ultrasonic cleaning on the B side of the polymer film 1, and the alcohol-soluble ink layer 12 on the B side of the polymer film 1 and the aluminum layer 3 on the surface of the alcohol-soluble ink layer 12 are cleaned to expose the polymer film 1; the ultrasonic power of the ultrasonic cleaning machine is 0.5 to 1.5 KW, and the ultrasonic time is 1 to 3 minutes; after cleaning, the composite microporous copper-aluminum foil current collector is obtained, such as Figure 6 As shown, the micropores 11 on the high molecular polymer film 1 connect the copper layer 2 and the aluminum layer 3 on both sides.

[0049] Step 10: Drop the reagent on the upper surface of the composite microporous copper-aluminum foil, stick a piece of PH test paper on the lower surface of the composite microporous copper-aluminum foil, observe the color change time of the PH test paper, and cut the composite microporous copper-aluminum foil for tensile strength test. Specifically, the reagent is lithium-ion electrolyte, and the electrolyte is dripped on the upper surface of the composite microporous copper-aluminum foil with a pipette, and a piece of PH test paper is attached to the lower surface of the composite microporous copper-aluminum foil. The color change time of the PH test paper is observed to detect the lithium-ion electrolyte permeability; then, 5.1g PVDF is weighed and dissolved in 67.8g NMP, stirred for 2h, 81.6g CNT is added, stirred for 2h, 500.8g ternary material is added, 24.7g NMP is added, and stirred for 3h to prepare the positive electrode slurry, and 1 spoonful of slurry is transferred with a small spoon to the upper surface of the composite microporous copper-aluminum foil, and a piece of PH test paper is attached to the lower surface of the composite microporous copper-aluminum foil, and the color change time of the PH test paper is observed to detect the slurry permeability; finally, a composite microporous copper-aluminum foil with a size of 100*25mm is cut with a sampler, and the gauge length of the room temperature tensile mechanical properties test is 50mm, the test rate is 5mm / min, and the tensile strength is recorded.

[0050] serial number Inkjet printing oil spot diameter um Inkjet printing oil spot spacing um Example 1 0.5 2 Example 2 1 4 Example 3 1.5 6 Example 4 2 8

[0051] Table 1 Implementation Scheme Table

[0052] Embodiment 1:

[0053] Copper plating layer on the A side of polymer film: Corona parameters: electrode gap: 1.5mm; corona voltage: 10000V; corona power: 3kw; corona speed 10m / min; inkjet printing oil spot diameter 0.5um, oil spot horizontal and vertical distance 2um; magnetron sputtering process conditions: background vacuum 5×10 至4 Pa, sputtering gas pressure 0.3 Pa, the distance between the target and the substrate is 50 mm, the sputtering power is 5.5 kW, and the copper electroplating time is 36 min.

[0054] Aluminum coating on the B side of the polymer film: Corona parameters: electrode gap: 1.5mm; corona voltage: 10000V; corona power: 3kw; corona speed: 10m / min; inkjet printing oil spot diameter 0.5um, oil spot horizontal and vertical distance 2um; evaporation process conditions: number of crucibles: 6; evaporation rate: 8g / min; coating speed: 1m 2 / min.

[0055] Embodiment 2:

[0056] Copper plating layer on the A side of polymer film: Corona parameters: electrode gap: 1.5mm; corona voltage: 10000V; corona power: 3kw; corona speed 10m / min; inkjet printing oil spot diameter 1um, oil spot horizontal and vertical distance 4um; magnetron sputtering process conditions: background vacuum 5×10至4 Pa, sputtering gas pressure 0.3 Pa, the distance between the target and the substrate is 50 mm, the sputtering power is 5.5 kW, and the copper electroplating time is 36 min.

[0057] Aluminum coating on the B side of the polymer film: Corona parameters: electrode gap: 1.5mm; corona voltage: 10000V; corona power: 3kw; corona speed: 10m / min; inkjet printing oil spot diameter 1um, oil spot horizontal and vertical distance 4um; evaporation process conditions: number of crucibles: 6; evaporation rate: 8g / min; coating speed: 1m 2 / min.

[0058] Embodiment three:

[0059] Copper plating layer on the A side of polymer film: Corona parameters: electrode gap: 1.5mm; corona voltage: 10000V; corona power: 3kw; corona speed 10m / min; inkjet printing oil spot diameter 1.5um, oil spot horizontal and vertical distance 6um; magnetron sputtering process conditions: background vacuum 5×10 至4 Pa, sputtering gas pressure 0.3 Pa, the distance between the target and the substrate is 50 mm, the sputtering power is 5.5 kW, and the copper electroplating time is 36 min.

[0060] Aluminum coating on the B side of the polymer film: Corona parameters: electrode gap: 1.5mm; corona voltage: 10000V; corona power: 3kw; corona speed 10m / min; inkjet printing oil spot diameter 1.5um, oil spot horizontal and vertical distance 6um; evaporation process conditions: number of crucibles: 6; evaporation rate: 8g / min; coating speed: 1m 2 / min.

[0061] Embodiment 4:

[0062] Copper plating layer on the A side of polymer film: Corona parameters: electrode gap: 1.5mm; corona voltage: 10000V; corona power: 3kw; corona speed 10m / min; inkjet printing oil spot diameter 2um, oil spot horizontal and vertical distance 8um; magnetron sputtering process conditions: background vacuum 5×10 至4 Pa, sputtering gas pressure 0.3 Pa, the distance between the target and the substrate is 50 mm, the sputtering power is 5.5 kW, and the copper electroplating time is 36 min.

[0063] Aluminum coating on the B side of the polymer film: Corona parameters: electrode gap: 1.5mm; corona voltage: 10000V; corona power: 3kw; corona speed: 10m / min; inkjet printing oil spot diameter 2um, oil spot horizontal and vertical distance 8um; evaporation process conditions: number of crucibles: 6; evaporation rate: 8g / min; coating speed: 1m 2 / min.

[0064]

[0065] Table 2 Experimental results

[0066] From the results of Example 1 to Example 4, the diameter of the inkjet printed oil spot increased from 0.5um to 2um, the inkjet printed oil spot spacing increased from 2um to 8um, the electrolyte penetration time was about 8min, and the tensile strength was slightly reduced. From Example 1 to Example 4, the slurry could not penetrate.

[0067] Refer to the instruction manual Figure 8 and Fig. 9, use a pipette to absorb the electrolyte droplets on the upper surface of the composite microporous copper-aluminum foil, and stick a piece of PH test paper on the lower surface of the composite microporous copper-aluminum foil. Observe the color change time of the PH test paper to test the lithium ion electrolyte permeability. In order to reduce experimental consumables, the selected PH test paper and composite microporous copper-aluminum foil are both small. Since the A and B surfaces of the composite microporous copper-aluminum foil are plated with a metal layer, there will be creases on the surface after bending. After pouring the lithium ion electrolyte on the composite microporous copper-aluminum foil for testing, due to the existence of creases and the bending of the composite microporous copper-aluminum foil, the lithium ion electrolyte will flow on the composite microporous copper-aluminum foil under the action of gravity, resulting in the PH test paper on the lower surface of the composite microporous copper-aluminum foil, The lithium ion electrolyte that cannot be completely adsorbed through the composite microporous copper-aluminum foil is not easy to be detected, resulting in a low efficiency of reading the pH test paper. To solve this problem, specifically, a device used in a method for making a composite microporous copper-aluminum current collector includes a support table 4, a processing station 5 and a driving mechanism 6 are arranged on the support table 4, the processing station 5 is used to place the object to be tested, the driving mechanism 6 includes a moving seat 63, and a regulating mechanism 7 is arranged on the moving seat 63. The regulating mechanism 7 includes a sleeve 72, and the sleeve 72 makes the object to be tested fit closely with the bottom of the sleeve 72 by applying downward pressure. A visual recognition instrument 8 is arranged in the support table 4, and the collection end of the visual recognition instrument 8 is arranged toward the sleeve 72. The processing station 5 includes a support seat 51, a through hole 1 is opened on the support seat 51, and a hole 2 is opened on the support table 4. The through hole 1 is connected to the through hole 2, and a transparent glass 52 is slidably arranged in the support seat 51. The driving mechanism 6 includes a linear driver 1 61, which is fixedly arranged on the support platform 4, a linear driver 2 62 is slidably arranged on the output shaft of the linear driver 1 61, and a moving seat 63 is fixedly arranged on the output shaft of the linear driver 2 62. The regulating mechanism 7 includes a connecting pipe 71, which is fixedly arranged on the moving seat 63, a sleeve 72 is fixedly connected to the connecting pipe 71, and a flexible gasket is fixedly arranged at the bottom end of the sleeve 72.

[0068] It should be noted that the linear drive 1 61 and the linear drive 2 62 are both configured as linear motors, the linear drive 2 62 is fixedly disposed on the output shaft of the linear drive 1 61, and the moving seat 63 is fixedly disposed on the output shaft of the linear drive 2 62. The visual recognition instrument 8 obtains the color change information of the PH test paper through a camera, which is a mature prior art and will not be described in detail here.

[0069] It should also be noted that in order to improve the brightness of the visual recognition device 8 during recognition, and thus improve the recognition accuracy of the visual recognition device 8 , an auxiliary light can be installed in the sleeve 72 .

[0070] In this embodiment, the PH test paper is placed on the transparent glass 52, and then the composite microporous copper-aluminum foil is placed on the PH test paper, and then the linear drive 1 61 and the linear drive 2 62 are started to drive the movable seat 63 to move downward, and the movable drive sleeve 72 of the movable seat 63 moves downward, so that the flexible gasket at the bottom of the sleeve 72 is tightly fitted with the surface of the composite microporous copper-aluminum foil, and the flexible gasket positions the composite microporous copper-aluminum foil and the PH test paper, so that the composite microporous copper-aluminum foil in the sleeve 72 and the composite microporous copper-aluminum foil outside are sealed, and then reagents such as lithium ion electrolyte or slurry are added to the sleeve 72 through the connecting tube 71, and the reagent passing through the composite microporous copper-aluminum foil is observed by the visual recognition instrument 8, that is, the time when the reagent color changes to judge its performance, so as to avoid preventing the reagent from flowing on the surface of the composite microporous copper-aluminum foil.

[0071] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.

Claims

1. A method for preparing a composite microporous copper-aluminum current collector, characterized in that: The following steps are involved: Step 1: using a polymer film (1) as a substrate, the polymer film (1) is provided with micropores (11), setting the dyne value of the surface of the polymer film (1) to 32 mN / m, and processing the A surface of the polymer film (1) using a corona machine; Step 2: using an inkjet printer to print a layer of alcohol-soluble ink (12) on the A side of the high molecular polymer film (1); Step 3: using magnetron sputtering to plate a copper layer (2) on the A surface of the polymer film (1), the target material being pure copper with a purity of 99.99%; Step 4: placing the polymer film (1) in an ultrasonic cleaning machine for the first cleaning, wherein the cleaning solvent is set to ethanol, and the alcohol-soluble ink layer (12) on the A side of the polymer film (1) and the copper layer (2) on the surface of the alcohol-soluble ink layer (12) are cleaned to expose the polymer film (1); Step 5: Place the polymer film (1) in an electroplating solution for copper electroplating, wherein the apparent current density in the electroplating solution is 2A / cm 2 , the electrodeposition time is 27 to 45 min; Step 6: placing the polymer film (1) in an ultrasonic cleaning machine for a second cleaning, wherein the cleaning solvent is set to ethanol; Step 7: Turn over the polymer film (1), and repeat steps 1 and 2 to process the B side of the polymer film (1); Step 8: using vacuum evaporation to plate an aluminum layer (3) on the B surface of the high molecular polymer film (1); Step 9: Repeat step 4 to perform ultrasonic cleaning on the B surface of the polymer film (1), so that the alcohol-soluble ink layer (12) on the B surface of the polymer film (1) and the aluminum layer (3) on the surface of the alcohol-soluble ink layer (12) are cleaned to expose the polymer film (1); Step 10: Drop the reagent on the upper surface of the composite microporous copper-aluminum foil, stick a piece of PH test paper on the lower surface of the composite microporous copper-aluminum foil, observe the color change time of the PH test paper, and cut the composite microporous copper-aluminum foil for tensile strength test.

2. The method for preparing a composite microporous copper-aluminum current collector according to claim 1, characterized in that: In step 2, the dyne value of the alcohol-soluble ink layer (12) on the surface of the high molecular polymer film (1) is 36mN / m±1mN / m; the diameter of the circular spot of the alcohol-soluble ink layer (12) is 0.1 to 10um, and the horizontal or vertical distance of the circular spot of the alcohol-soluble ink layer (12) is 0.4 to 40um.

3. The method for preparing a composite microporous copper-aluminum current collector according to claim 2, characterized in that: In step 3, the distance between the target and the substrate is 40 mm to 60 mm, the sputtering power is 4.5 kW to 6.5 kW; and the thickness of the copper layer (2) is 50 to 60 nm.

4. The method for preparing a composite microporous copper-aluminum current collector according to claim 3, characterized in that: In step 4, the ultrasonic power of the ultrasonic cleaning machine is 0.5 to 1.5 KW, and the ultrasonic time is 1 to 3 minutes.

5. The method for preparing a composite microporous copper-aluminum current collector according to claim 4, characterized in that: In step 5, the electroplating solution uses deionized water as solvent, and is stirred and prepared according to the concentration of CuSO4 of 200g / L and the concentration of concentrated H2SO4 of 60g / L; the electroplating copper uses 99.99% pure copper as the anode target, and the copper-plated film after S4 treatment is placed in the electroplating solution for electroplating copper, the apparent current density is 2A / cm2, and the electroplating time is 27 to 45min; the thickness of the copper layer (2) is 1.5 to 2.5um.

6. The method for preparing a composite microporous copper-aluminum current collector according to claim 5, characterized in that: The reagent in step ten is lithium ion electrolyte. The electrolyte is sucked by a pipette and dropped on the upper surface of the composite microporous copper-aluminum foil. A piece of PH test paper is attached to the lower surface of the composite microporous copper-aluminum foil. The color change time of the PH test paper is observed to perform lithium ion electrolyte permeability detection.

7. A device used in the method for making the composite microporous copper-aluminum current collector according to claim 6, characterized in that: The invention comprises a support platform (4), wherein a processing station (5) and a driving mechanism (6) are arranged on the support platform (4), wherein the processing station (5) is used to place an object to be tested, wherein the driving mechanism (6) comprises a movable seat (63), wherein a regulating mechanism (7) is arranged on the movable seat (63), wherein the regulating mechanism (7) comprises a sleeve (72), wherein the sleeve (72) makes the object to be tested fit tightly with the bottom of the sleeve (72) by applying downward pressure, and wherein a visual recognition instrument (8) is arranged inside the support platform (4), wherein a collection end of the visual recognition instrument (8) is arranged toward the sleeve (72).

8. The device used in the method for making the composite microporous copper-aluminum current collector according to claim 7 is characterized in that: The processing station (5) comprises a support seat (51), a through hole 1 is formed on the support seat (51), a hole 2 is formed on the support platform (4), the through hole 1 is connected to the through hole 2, and a transparent glass (52) is slidably arranged in the support seat (51).

9. The device used in the method for making the composite microporous copper-aluminum current collector according to claim 8, characterized in that: The driving mechanism (6) comprises a linear drive 1 (61), wherein the linear drive 1 (61) is fixedly arranged on the support platform (4), a linear drive 2 (62) is slidably arranged on the output shaft of the linear drive 1 (61), and the moving seat (63) is fixedly arranged on the output shaft of the linear drive 2 (62).

10. The device used in the method for making the composite microporous copper-aluminum current collector according to claim 9, characterized in that: The regulating mechanism (7) comprises a connecting pipe (71), the connecting pipe (71) is fixedly arranged on the movable seat (63), the sleeve (72) is fixedly connected to the connecting pipe (71), and a flexible gasket is fixedly arranged at the bottom end of the sleeve (72).